STRUCTURE AND CHARACTERISTICS OF HIGH-PHOSPHOROUS CAST IRONS AND CAST IRONS WITH BALL-SHAPE GRAPHITE - A. M. Saikov; K. V. Serikov; E. I. Marukovich; V. M. Karpenko (Литьë и металлургия)
There are given the structure and characteristics of high-phosphorous cast irons and cast irons with ball-shape graphite in the article.